2003
DOI: 10.1074/jbc.m305825200
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation Factor-dependent Phospholipase D Activation by the M3 Muscarinic Receptor

Abstract: G protein-coupled receptors can potentially activate phospholipase D (PLD) by a number of routes. We show here that the native M 3 muscarinic receptor in 1321N1 cells and an epitope-tagged M 3 receptor expressed in COS7 cells substantially utilize an ADP-ribosylation factor (ARF)-dependent route of PLD activation. This pathway is activated at the plasma membrane but appears to be largely independent of G q/11 , phospholipase C, Ca 2؉ , protein kinase C, tyrosine kinases, and phosphatidyl inositol 3-kinase. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 71 publications
5
58
1
Order By: Relevance
“…In some cases, another ARF family member may regulate the process. Indeed, some receptors have been found in complex with ARF1 (31)(32)(33). Even if this ARF isoform is mainly present on membranes of intracellular organelles such as the Golgi (34,35), its presence at the plasma membrane has been previously reported (36).…”
Section: Reduction Of Arf6mentioning
confidence: 99%
“…In some cases, another ARF family member may regulate the process. Indeed, some receptors have been found in complex with ARF1 (31)(32)(33). Even if this ARF isoform is mainly present on membranes of intracellular organelles such as the Golgi (34,35), its presence at the plasma membrane has been previously reported (36).…”
Section: Reduction Of Arf6mentioning
confidence: 99%
“…ARF1 is mainly found in the Golgi apparatus and acts to promote carrier vesicle biogenesis by nucleating the assembly of coat protein complexes at sites of vesicle formation (Stearns et al, 1990). Several reports have suggested that ARF1 can also localize to the plasma membrane transmitting signals from transmembrane proteins (Galas et al, 1997;Mitchell et al, 2003;Cohen et al, 2007;Boulay et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors are members of a family of receptors that are coupled to heterotrimeric transducer G proteins. The M 1 , M 3 , and M 5 acetylcholine receptor subtypes are efficiently coupled to the pertussis toxin-insensitive G␣ q/11 and G 13 subtype G proteins, leading to activations of PLC and PLD, whereas the M 2 , and M 4 receptors are coupled to pertussis toxin-sensitive G i and G 0 subtype G proteins (27)(28)(29). The mechanism of PLD activation by the muscarinic receptor has been mainly studied for the M 3 receptor subtype.…”
mentioning
confidence: 99%